2001
DOI: 10.1096/fj.00-0351com
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein 3 transcription is regulated by peroxisome proliferator‐activated receptor α in the adult rodent heart

Abstract: Relatively little is known concerning the regulation of uncoupling proteins (UCPs) in the heart. We investigated in the adult rodent heart 1) whether changes in workload, substrate supply, or cytokine (TNF-alpha) administration affect UCP-2 and UCP-3 expression, and 2) whether peroxisome proliferator-activated receptor alpha (PPARalpha) regulates the expression of either UCP-2 or UCP-3. Direct comparisons were made between cardiac and skeletal muscle. UCP-2, UCP-3, and PPARalpha expression were reduced when ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
172
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(188 citation statements)
references
References 50 publications
14
172
2
Order By: Relevance
“…These results suggested that the extracardiac effects of the PPAR-␣ agonist, by decreasing circulating free fatty acid levels and increasing insulin sensitivity, have greater effects on cardiac energy utilization by decreasing the activation of PPAR-␣ and the substrate availability of FAO enzymes rather than directly inducing their expression in the heart. This conclusion is consistent with the requirement of fatty acid substrates to activate PPAR-␣-dependent fatty acid uptake and FAO by cultured neonatal cardiomyocytes (10,91,92) and the direct correlation between UCP-3 expression in adult rat hearts and dietary fat intake by these animals (103). Although the Aasum et al study (1) also showed a 46% decrease in myocardial TG content after a 4-to 5-wk treatment with a PPAR-␣ agonist, they did not show improvements in contractile function of the myocardium.…”
Section: Ppar-␣ and The Heartsupporting
confidence: 84%
See 1 more Smart Citation
“…These results suggested that the extracardiac effects of the PPAR-␣ agonist, by decreasing circulating free fatty acid levels and increasing insulin sensitivity, have greater effects on cardiac energy utilization by decreasing the activation of PPAR-␣ and the substrate availability of FAO enzymes rather than directly inducing their expression in the heart. This conclusion is consistent with the requirement of fatty acid substrates to activate PPAR-␣-dependent fatty acid uptake and FAO by cultured neonatal cardiomyocytes (10,91,92) and the direct correlation between UCP-3 expression in adult rat hearts and dietary fat intake by these animals (103). Although the Aasum et al study (1) also showed a 46% decrease in myocardial TG content after a 4-to 5-wk treatment with a PPAR-␣ agonist, they did not show improvements in contractile function of the myocardium.…”
Section: Ppar-␣ and The Heartsupporting
confidence: 84%
“…Studies using cultured neonatal cardiomyocytes have demonstrated the direct effects of fatty acids and PPAR-␣ agonists in activating PPAR-␣-dependent enzymes of fatty acid uptake and FAO in the heart (10,91,92). In vivo studies in adult rats showed that expression of myocardial uncoupling protein 3, a PPAR-␣-dependent enzyme, was increased on a highfat diet and decreased on a low-fat diet (103). These results suggest that the circulating levels of TGs and fatty acids are important determinants of substrate availability for myocardial PPAR-␣ and FAO.…”
Section: Ppar-␣ and The Heartmentioning
confidence: 86%
“…Cardiac-specific overexpression of PPAR␣ also results in enhanced cardiac PDK4 mRNA expression, which is further augmented when the PPAR␣-overexpressing transgenic mice are chronically treated with WY-14643 as a component of the diet (10). Conversely, cardiac PDK4 mRNA expression is suppressed in pressure overload cardiac hypertrophy (72), where cardiac PPAR␣ expression and activity are suppressed (1). These data indicate that modulation of PPAR␣ expression can influence PDK4 expression.…”
Section: Regulation Of Mammalian Pdk4 Expression By Pparsmentioning
confidence: 86%
“…Thus mechanisms in addition to signaling via PPAR␣ contribute to the regulation of cardiac PDK4 expression in starvation. Within this context, both prolonged starvation and experimental diabetes, conditions associated with increased cardiac FA utilization, have been reported to suppress cardiac PPAR␣ expression (72). A comparison of the responses of cardiac PDK isoform protein expression to PPAR␣ activation by WY-14643 in fed and starved rats over a timescale comparable to that over which effects of starvation can be observed (24 h) failed to demonstrate an effect of PPAR␣ activation on cardiac PDK4 protein expression (16).…”
Section: Regulation Of Mammalian Pdk4 Expression By Pparsmentioning
confidence: 99%
“…In contrast, contradictory conclusions about the role of PPARα on DM have also been documented (Baraka & AbdelGawad, 2010; Young et al., 2001). CMs chronically exposed to FA showed relatively lower PPARα expression and treated with the PPAR agonist fenofibrate showed suppression of PA‐induced apoptosis (Young et al., 2001). We propose that the model and treatment style differences among these studies account for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%